PENGANCAMAN BERUPA PUNGUTAN LIAR PADA PELAKU USAHA (Studi Putusan Nomor : 1791/PID.B/2015/PN MDn) - Sonya Airini Batubara; Immanuel R C S Pelawi; Lina Wati (Universitas Muhammadiyah Ponorogo, 2023)
The development of today's era greatly affects the development of people's behavior. At present, moral and economic issues are some examples of the problems faced by our nation which ultimately lead to many crimes, such as illegal levies which are certainly very disturbing to the community. Not only do levies unofficially but also threats and violence using sharp weapons to parties who are in a weak position because of an interest. That is why illegal levies (extortion) lead to acts of extortion mentioned in the criminal law book. The Criminal Code actually regulates several crimes that can be imposed on perpetrators of extortion, one of which is Article 368 paragraph (1) which regulates extortion and threats for which the sentence is nine years. Synergy in law enforcement against extortion is highly expected for the sake of creating security in society, especially business actors.